Our Separate Ways: Black and White Women and the Struggle for Professional IdentityOur Separate Ways: Black and White Women and the Struggle for Professional Identity, by BellElla L. J. Edmondson and NkomoStella M. Boston: Harvard Business School Press, 2001. - Putnam, Linda L. (Academy of Management Review, 2003)
The article presents a review of the book ?Our Separate Ways: Black and White Women and the Struggle for Professional Identity,? by Ella L. J. Edmondson Bell and Stella M. Nkomo.